Characterization of molecules involved in protein translocation using a specific antibody. - David I. Meyer; Daniel Louvard; B Dobberstein (1982)
The vectorial translocation of nascent proteins through the membrane of the rough endoplasmic reticulum has been shown to require a specific membrane-bound protein whose cytoplasmic domain can be proteolytically cleaved and isolated as an active peptide of mol wt 60,000 (Meyer and Dobberstein, 1980, J. Cell Biol. 87:503-508). Rabbit antibodies raised against this peptide were used to further characterize the membrane-bound molecule. Immunoprecipitation of solubilized, radiolabeled rough microsomal proteins yielded a single polypeptide of mol wt 72,000, representing the membrane-bound protein from which the 60,000-mol wt peptide was proteolytically derived. The antibody could also be used to remove exclusively the 60,000-mol wt peptide, and thus the translocation activity, from elastase digests tested in a reconstituted system. Moreover, immunoprecipitation of elastase extracts alkylated with [14C] N-ethylmaleimide selected a single species of mol wt 60,000. Immunoprecipitation of in vivo radiolabeled proteins from the appropriate cell type yielded the 72,000-mol wt membrane protein irrespective of the duration of labeling, or if followed by a chase. Subsequent treatment with protease generated the 60,000-mol wt fragment. In addition, the antibody could be used to visualize reticular structures in intact cells which correspond to endoplasmic reticulum at the ultrastructural level. It is thus clear that one membrane component required in the vectorial translocation of nascent secretory (and membrane) proteins is a peptide of mol wt 72,000.